دور الرقابة المالية في مكافحة الفساد المالي في الجماعات الإقليمية الجزائرية The Role of Financail Control in fighting against Financail Corruption in Algerian Territorial Groups - ورغي عبلة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2024)
من منطلق أن الرقابة المالية تعد من أهم آليات مكافحة الفساد المالي تساءلنا حول كيفية اسهامها في تحقيق ذلك في الجماعات الإقليمية الجزائرية، وهل صحيح أن منع وقوع الأخطاء والمخالفات المالية هو قوامها في ذلك. لتّحقق من مدى صحة ذلك والإجابة عن التساؤل المطروح اعتمادنا على المنهج التحليلي والقانوني والاستقرائي، وكذا على خطة ثنائية مفصلة لموضوع الدراسة، لتتوصل الدراسة إلى أن كشف ومنع وقوع الأخطاء والمخالفات المالية، والعمل على تصحيحها، هو بمثابة منهاج الرقابة المالية في مكافحة الفساد المالي في الجماعات الإقليمية الجزائرية. Abstract On the basis of the fact that financial control is one of the most important mechanisms for combating financial corruption, we wondered how it contributes to the achievement of this in the Algerian Territorial groups, and is it true that preventing the occurrence of errors and financial irregularities is its strength in that? In order to check the validity of this and answer the question raised, we relied on the analytical, legal and inductive approach, as well as on a detailed bilateral plan for the subject of the study, so that the study concludes that the detection and prevention of financial errors and irregularities, and working to correct them, is a financial control approach in combating financial corruption in Algerian Territorial groups.